2005
DOI: 10.1007/s10705-005-3108-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Straw Application on Rice Yields and Nutrient Availability on an Alkaline and a pH-neutral Soil in a Sahelian Irrigation Scheme

Abstract: Like elsewhere in the Sahel, actual rice yields (3-5 t ha À1 ) are far below yield potential (±8 t ha À1 ) in an irrigation scheme in central southern Mauritania. Earlier studies showed that yields are especially low on alkaline soils due to N and P deficiency. We investigated the potential of rice straw application as a mean to improve yields and fertilizer efficiency on an alkaline soil (pH 8.2) and a pH-neutral soil (pH 6.2). Application of 5 t straw ha À1 increased yields by 1.1 t ha À1 on average, indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In this experiment, mulching with the straw of Trifolium repens , Conyza Canadensis, and Stellaria media increased the root, stem, leaf, shoot and whole‐plant biomasses of Cyphomandra betacea seedlings compared with the control under Cd stress (Table ). These results were the same as studies using straws of other plant species which also increasing the crop yield . However, compared with the control, mulching with Eclipta prostrata straw decreased the root, stem, leaf, shoot and whole‐plant biomasses of Cyphomandra betacea seedlings (Table ), indicating that not all straws of plant species could promote the growth of other plant species.…”
Section: Resultssupporting
confidence: 73%
“…In this experiment, mulching with the straw of Trifolium repens , Conyza Canadensis, and Stellaria media increased the root, stem, leaf, shoot and whole‐plant biomasses of Cyphomandra betacea seedlings compared with the control under Cd stress (Table ). These results were the same as studies using straws of other plant species which also increasing the crop yield . However, compared with the control, mulching with Eclipta prostrata straw decreased the root, stem, leaf, shoot and whole‐plant biomasses of Cyphomandra betacea seedlings (Table ), indicating that not all straws of plant species could promote the growth of other plant species.…”
Section: Resultssupporting
confidence: 73%
“…Therefore, soil acidification is effective in improving the N availability of soil previously under monocropped aerobic rice cultivation. Van Asten et al. (2005) also reported that N availability and N uptake were significantly higher on pH‐neutral soil than on more alkaline soil.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, legumes increased rice yields by 0.23 Mg ha -1 , while some five selected legumes raised rice yields from 0.32 to 1 Mg ha -1 (Table 3). In Mauritania, application of N fertilizer increased rice yields, and addition of straw had a positive effect, independent of fertilizer dose or soil type (van Asten et al 2005). On neutral soils, NRE ranged from 0.32 kg kg -1 in the absence of P to 0.41 kg kg -1 when P was added, and further increased to 0.52 kg kg -1 in the presence of rice straw.…”
Section: Resultsmentioning
confidence: 98%